Digitizing TB Monitoring: A Study of SISFOTBPARU in Bandar Lampung - Sri Indra Trigunarso; Zainal Muslim; Amrul Hasan (Poltekkes Kemenkes Tanjung Karang, 2026)
The pulmonary tuberculosis patient treatment monitoring information system (SISFOTBPARU) application still needs further development to ensure the implemented features function optimally. In this method, usability testing and evaluation are used to increase user satisfaction. Usability can also be used to improve usability in user interactions on the site. This study measures the level of usability of the pulmonary tuberculosis patient treatment monitoring information system (SISFOTBPARU) application website. Usability measurements are conducted to assess whether user interaction with the website is smooth and whether users can achieve their goals while visiting it. This research is quantitative, using the System Usability Scale (SUS) with 10 questions as a benchmark for usability assessment, and one open-ended question to gather information on the needs of 30 users when visiting the website. The results of the SUS measurement on the SISFOTBPARU website yielded a score of 89.76, with acceptability classified as marginally high and grade scales including A, indicating a very good level of usability. Meanwhile, hypothesis testing indicates that the developed application has a positive, significant impact on patient self-care management. This application is expected to be used in more health facilities.